Perception of urinary incontinence (UI) among women in Poland - Radziszewski, Piotr; Bender, Sylwia; Borowski, Jacek; Borkowski, Tomasz; Bres-Niewada, Ewa; Borkowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2011)
Objectives: Assessment of perception of urinary incontinence (UI) among women in Poland. Materials and methods : The Centre for Public Opinion Research TNS OBOP conducted a multisubject thematic, face-to-face interview, in the homes of respondents. Questioning about the quality of life was carried on in two successive editions of the survey from 4 to 7 and from 11 to 14 February 2010. The study was performed on a nationwide random sample of 855 women aged 35 and older. Results : The most troublesome consequences of UI are odour (44%), leaking of urine (43%), lack of control over own body (31%), unexpected search for toilets (24%), feeling of moisture (22%) and fear of the reaction of others (15%). Most frequently indicated ways to improve the quality of life for women with UI are a visit to the doctor (57%), the use of anatomical inserts (33%) and pelvic floor muscle exercise (21%). Sense of attractiveness is retained for 53% of Polish women with UI, 25% do not feel attractive as a woman and 22% have no opinion on this subject. Conclusion : The problem of UI is common and is associated with reduction in quality of life. However, those who benefit from medical consultations, hygiene products (anatomical pads) or pelvic floor muscle exercises often retain a sense of attractiveness.